2016
DOI: 10.1021/acschemneuro.5b00178
|View full text |Cite
|
Sign up to set email alerts
|

Double Blockade of Glioma Cell Proliferation and Migration by Temozolomide Conjugated with NPPB, a Chloride Channel Blocker

Abstract: Glioblastoma is the most common and aggressive primary malignant brain tumor. Temozolomide (TMZ), a chemotherapeutic agent combined with radiation therapy, is used as a standard treatment. The infiltrative nature of glioblastoma, however, interrupts effective treatment with TMZ and increases the tendency to relapse. Voltage-gated chloride channels have been identified as crucial regulators of glioma cell migration and invasion by mediating cell shape and volume change. Accordingly, chloride current inhibition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 45 publications
(78 reference statements)
0
11
0
Order By: Relevance
“…Malignant gliomas often recur within 1-2 cm of the original tumor site because of the tumor cell invasion into the surrounding normal brain tissue where they can evade surgical removal and radiation therapy. In view of this disadvantage of the current therapeutic method, efforts on exploring the reliable therapeutic targets based on identifying the molecular pathological process of gliomas, might provide a better cure and therapy for glioma (14) . In the present study, we confirmed the key role of Gli1-AQP1 signal pathway in glioma cell metastasis and survival.…”
Section: Discussionmentioning
confidence: 99%
“…Malignant gliomas often recur within 1-2 cm of the original tumor site because of the tumor cell invasion into the surrounding normal brain tissue where they can evade surgical removal and radiation therapy. In view of this disadvantage of the current therapeutic method, efforts on exploring the reliable therapeutic targets based on identifying the molecular pathological process of gliomas, might provide a better cure and therapy for glioma (14) . In the present study, we confirmed the key role of Gli1-AQP1 signal pathway in glioma cell metastasis and survival.…”
Section: Discussionmentioning
confidence: 99%
“…The interesting conclusions drawn in this work were that no single compound in the Compound Kushing Injection mixture accounted for the full therapeutic effect of the whole extract; combinations of agents were required to reconstitute the beneficial activity, and the most effective combinations of compounds depended on the cancer cell type. Combined block of glioma cells with 5-nitro-2-(3-phenylpropylamino)-benzoate (a nonspecific chloride channel blocker), covalently linked to temozolomide (an oral chemotherapeutic drug for glioblastoma) suppressed glioma cell proliferation, migration, and invasion (Park et al, 2016). Temozolomide modifies DNA or RNA at guanine and adenine bases by addition of methyl groups (Lee, 2016); however, a substantial proportion of tumors are insensitive to temozolamide due to expression of methyltransferase genes.…”
Section: Pharmacological Targets For Cancer Treatmentmentioning
confidence: 99%
“…Thus, Cl À ions also play an important role in glioma cell migration and invasion. One of the voltage-gated chloride channel, CLC-3, encoded by the CLCN3 gene, has also been recognized as a crucial regulator of glioma cell migration and invasion by modulating cellular shape and volume (10,(20)(21)(22). CLC-3 is highly expressed on the plasma membrane of glioma cells compared with the normal brain.…”
Section: Ion Channels and Glioma Invasion/ Migrationmentioning
confidence: 99%